A descriptive study of the migration of skilled garment workers effects on selected garment manufacturers - Santos, Marivic P.
This is a descriptive research on the migration of skilled garment workers and its effects on selected garment manufacturers. This study answered the following questions: 1) How many skilled Filipino garment workers left to work abroad from 2000 to 2008? 2) What were the skills categories of these migrant garment workers? 3) What countries hosted the majority of the skilled garment workers? 4) How did losing skilled garment workers affected selected local garment manufacturers? 5) How did the selected garment manufacturers cope with the migration-related problems? The study used analysis of secondhand data and survey research. To determine the effects of migration on garment manufacturers, purposive sampling method was used. Ten garment manufacturers were selected for the study. The researcher developed a questionnaire and analyzed the results of the survey through using simple statistical tools. The deployment data showed that from 2000 to 2008, almost 50,000 Filipino sewers, embroiderers, tailors, dressmakers, cutters, and patternmakers left the country to work abroad. Most of these workers were women. The top destination for the migrant garment workers was Saudi Arabia. The other host countries for them were United Arab Emirates, Brunei Darussalam, Bahrain, and Taiwan. The survey on garment manufacturers showed that their former employees either transferred to other local garment companies or went abroad and held the same positions they previously had. The selected garment manufacturers did not find it hard to find replacements. Some of them hired applicants who did not have previous experience in garment manufacturing. The training for newly hired sewers usually lasted from less than a month to three month at the most. Cutters and patternmakers usually had longer training, which could last for more than six months. Some of the problem that the selected garment manufacturers encountered were delays in production, incapability to accept more orders, and quality problems. To solve these, the selected garment manufacturers used the following techniques: overtime, hiring highly skilled replacements, subcontracting, hiring and training applicants with no previous experience in garment manufacturing, and lateral transfer of existing employees. Majority of the selected garment manufacturers said that their former employees stayed with them for one to three years, some even longer. This study may serve as a model or guide for related studies on migration of skilled garment workers. Future researches may also consider comparing the actual demand for skilled garment workers here and abroad. Another area that can be studied is the rate of employee turnover in the local garment industry as well as its causes and effects.